The incidence of venous thromboembolism is low when risk stratification-based thromboprophylaxis is used after fast-track hip and knee arthroplasty - Annette M Moisander; Konsta Pamilo; Jukka Huopio; Hannu Kautiainen; Anne Kuitunen; Juha Paloneva (BMC Musculoskeletal Disorders, 2024)
Abstract Background The optimal length of thromboprophylaxis after total hip or knee arthroplasty (THA and TKA) is unknown. Fast-track protocols have improved patient care and led to shorter immobilization and length of stay (LOS) after THA and TKA, thereby diminishing venous thromboembolism (VTE) risk. Here, we investigated risk stratification-based thromboprophylaxis after fast-track THA and TKA. Methods A retrospective register study was conducted in two Finnish hospitals using a fast-track protocol for THA and TKA. These hospitals use risk stratification-based planning of thromboprophylaxis, including risk evaluation of patients’ personal VTE risk. Patients at low risk received thromboprophylaxis solely during hospitalization, provided this lasted five days or less. All VTEs and clinically relevant bleedings were obtained from Finnish hospital discharge registers between 1 January 2020 and 31 December 2021 to determine VTE incidences and clinically relevant bleedings 90 days after surgery. Results During the study period 3 713 arthroplasties were performed (1 636 THAs and 2 077 TKAs). The 90-day incidence of VTE was 0.7% (CI 0.4 to 0.9), and 25 VTEs occurred within 90 days of surgery. These VTEs comprised 12 pulmonary embolisms and 13 deep vein thromboses, none of which was fatal. The incidence of clinically relevant bleedings (n = 57) within 90 days of surgery was 1.5% (CI 1.1 to 1.9). One intracranial bleeding was fatal. The bleedings typically occurred at the operational site. Conclusion Risk stratification-based thromboprophylaxis appears safe for fast-track THA and TKA patients as the incidences of VTEs and clinically relevant bleedings were low.